20th Anniversary Update of the Ottawa Decision Support Framework Part 1: A Systematic Review of the Decisional Needs of People Making Health or Social Decisions. (July 2020) - Hoefel, Lauren; O'Connor, Annette M.; Lewis, Krystina B.; Boland, Laura; Sikora, Lindsey; Hu, Jiale; Stacey, Dawn
Background . The Ottawa Decision Support Framework (ODSF) has been used for 20 years to assess and address people's decisional needs. The evidence regarding ODSF decisional needs has not been synthesized.Objectives . To synthesize evidence from ODSF-based decisional needs studies, identify new decisional needs, and validate current ODSF decisional needs.Methods . A mixed-studies systematic review. Nine electronic databases were searched. Inclusion criteria: studies of people's decisional needs when making health or social decisions for themselves, a child, or a mentally incapable person, as reported by themselves, families, or practitioners. Two independent authors screened eligibility, extracted data, and quality appraised studies using the Mixed Methods Appraisal Tool. Data were analyzed using narrative synthesis.Results . Of 4532 citations, 45 studies from 7 countries were eligible. People's needs for 101 unique decisions (85 health, 16 social) were reported by 2857 patient decision makers ( n = 36 studies), 92 parent decision makers ( n = 6), 81 family members ( n = 5), and 523 practitioners ( n = 21). Current ODSF decisional needs were reported in 2 to 40 studies. For 6 decisional needs, there were 11 new (manifestations): 1) information (overload, inadequacy regarding others' experiences with options), 2) difficult decisional roles (practitioner, family involvement, or deliberations), 3) unrealistic expectations (difficulty believing outcome probabilities apply to them), 4) personal needs (religion/spirituality), 5) difficult decision timing (unpredictable), and 6) unreceptive decisional stage (difficulty accepting condition/need for treatment, powerful emotions limiting information processing, lacking motivation to consider delayed/unpredictable decisions).Limitations . Possible publication bias (only peer-reviewed journals included). Possible missed needs (non-ODSF studies, patient decision aid development studies, 3 ODSF needs added in 2006).Conclusion . We validated current decisional needs, identified 11 new manifestations of 6 decisional needs, and recommended ODSF revisions.